The Application of STAD in Teaching Reading of Narrative Text to the Eleventh Graders Of SMA Intensif Taruna Pembangunan Surabaya (RETAIN, 2013)
Abstrak Siswa percaya bahwa mereka masih mengalami kesulitan dalam kegiatan membaca. Jadi, guru harus kreatif dalam mengajar membaca. STAD disarankan untuk digunakan sebagai teknik pengajaran membaca. Teks yang sesuai untuk tugas membaca adalah narasi. Ada dua pertanyaan dalam penelitian ini, pertama adalah "Bagaimana penerapan STAD dalam pengajaran membaca teks narasi dengan menerapkan STAD pada siswa kelas XI SMA Taruna intensif Pembangunan Surabaya?" Dan "Bagaimana respon dari siswa kelas XI SMA Taruna Pembangunan Surabaya intensif setelah belajar dengan teknik STAD? ".Peneliti menggunakan desain deskriptif kualitatif untuk mendapatkan informasi. Data penelitian untuk pertanyaan penelitian pertama adalah guru dan kegiatan siswa yang diperoleh dari lembar observasi dan catatan lapangan. Kemudian data penelitian untuk pertanyaan penelitian kedua adalah respon yang diperoleh dari kuesioner yang diisi oleh siswa. Data diperoleh melalui observasi tiga kali selama tiga pertemuan yang berfokus pada bagaimana STAD ini diterapkan dalam pengajaran membaca teks naratif dan juga bagaimana respon siswa setelah STAD itu diterapkan dalam pengajaran membaca di kelas. STAD ini diterapkan di kelas. Para siswa dibagi menjadi kelompok-kelompok dan kemudian mereka diminta untuk mendiskusikan teks dengan kelompok mereka sendiri. Guru berpindah-pindah di kelas untuk memeriksa apakah siswa memiliki beberapa kesulitan atau tidak. Setelah sesi diskusi berakhir, guru memastikan bahwa semua siswa memahami teks dengan baik dengan membahas teks bersama-sama. Berdasarkan hasil penelitian, siswa tertarik untuk membaca teks narasi melalui teknik STAD karena mereka memiliki berbagai kegiatan dalam proses belajar mengajar. Hal itu membuat siswa lebih aktif dan prestasi yang lebih baik dalam hal membaca teks narasi. Hal ini ditunjukkan dari hasil respon siswa terhadap penerapan STAD di kelas mereka. STAD diyakini sebagai salah satu teknik alternatif yang membantu baik guru dan siswa dalam proses belajar mengajar membaca teks narasi. Diharapkan bahwa penelitian lebih lanjut akan dilakukan dengan teknik yang berbeda untuk memperkaya pemahaman kita tentang mengajar dalam membaca narasi. Abstract Students believe that they still have difficulty in reading activity. So, teacher should be creative in teaching of reading. STAD is suggested to be used as a technique in teaching reading. The appropriate text for reading task is narrative. There are two research questions in this study, first is “How is the application of STAD in teaching reading of narrative text by applying STAD to the eleventh graders of SMA Intensif Taruna Pembangunan Surabaya?” and “How is the response of the Eleventh Graders of SMA Intensif Taruna Pembangunan Surabaya after studying with STAD technique?” The researcher used descriptive qualitative design in order to obtain the information. The data of the study for the first research question was the teachers and the students’ activities that were obtained from observation checklist and field notes. Then the data of the study for the second research question was students’ responses that were obtained from students’ questionnaire. The data were obtained through three-time observation during three meetings that focused in how the STAD was applied in teaching reading of narrative text and also how the students’ responses after the STAD was applied in teaching reading in the class. The STAD is applied in the class. The students were divided into groups and then they were asked to discuss the text with their own group. The teacher moved around the class to check whether the students had some difficulties or not. After the discussion session ended, the teacher made sure that all the students understood the text well by discussing the text together. Based on the result, students were interested in reading narrative text through STAD technique because they had various activities in teaching and learning process. It made students more active in reading activity and better achievement in reading narrative text. It was shown from the result of students’ response toward the application of STAD in their class. The STAD was believed as one alternative technique which helped both of the teacher and the students in teaching and learning reading of narrative text. It was hoped that further research would be done with different techniques to enrich our understanding of teaching in narrative reading. INTRODUCTION Language is important since it is a means of communication. Through language, people tell stories, share ideas, give information, and so forth. Considering that there are five different continents with, definitely, different languages, it is such a task to master all languages existing in this world in order to be able to communicate with people from different countries. Fortunately, the solution of this barrier appears. English nowadays serves as lingua franca in many parts of the world. Lingua franca is a language widely adopted for communication between two speakers whose native languages are different from each other and where one or both are using it as a second language. Reading is one that can provide experience to the reader. People can enrich their vocabularies, build their knowledge and increase their skill in understanding a context of written discourse through reading. People can read any reading materials such as books, magazines, newspapers, and reports. Reading is a fluent process of reader in combining information from a text and their own background knowledge to build meaning. There are many students who have problem in learning reading skill at the classroom. One of the main factors is that the students find difficulties to understand the text in their class. Although the students understand the meaning of difficult words, they do not know the message in the text. It is caused by the condition that they are accustomed to understand the meaning of a difficult word in isolation; they find it difficult to comprehend the text well. There are several kinds of genre texts taught in junior high school in Indonesia; they are descriptive, recount, procedure, narrative, etc. Narrative text is a text that entertains and deals with problematic events, imaginations, experiences and time. The purpose of narrative text is to present a view of the world that entertains and to inform the reader or listener. Having the general purpose, narrative text also served to gain and hold the reader’s interest to a story. In addition to that, narrative text is organized to focus on character. It may be built by using descriptive, familiar language and dialogue. Many students also get some difficulties in reading narrative text because the monotonous way of teaching then they get bored and get low motivation. If an English class is conducted in interesting and attractive ways, the students can have high motivation in studying English. In this study, the researcher tried to use a technique called Cooperative Learning to make the class more interesting and attractive. Cooperative learning provides beneficial activities to the students. Here the students were divided into teams that provide them to interact. By interacting with peers, students understand the topic discussed more and easily since they use a simpler language. Cooperative Learning has many models and technique. One of them is Student Team Achievement Division (STAD). It is a type of Cooperative Learning where students learn in small group with heterogeneous members. It uses activity sheet or peripheral study which needs to be completed in study items. Then students need to help each other to comprehend study materials through tutorial, quiz and discussion. By using STAD, the students not only listen to the teacher and do other boring activities such as reading the whole text without understanding the message in the text, but they also participate and involve actively in the learning process. STAD makes the students easier to comprehend a text because it gives everyone opportunity to discuss the material with their group. So, STAD is very appropriate to be used to teach students. The researcher chooses Senior High school because English is taught as a local content course of study in this grade. The important task is the teacher should be able to motivate the students to learn and pay attention to the material which the teacher presents, so they do not get bored. In this study, the researcher wants to study “The Application of STAD in Teaching Reading of Narrative Text to the Eleventh Graders of SMA Intensif Taruna Pembangunan (ITP) Surabaya”. RESEARCH DESIGN This study used qualitative research because the researcher considered this studydescribed the class activities during teaching learning process and also analyzed the students’ responses while learning with STAD in reading narrative text class. The data that was collected was in the form of word or pictures rather than numbers. The written results of the research contained quotations from the data to illustrate and substantiate the presentation. “The data included interview, transcripts, field notes, photographs, videotapes, personal documents, memos, and other official records. In their search for understanding, qualitative researchers do not reduce the pages upon pages of narration and other data to numerical symbols. They try to analyze it with all its richness as closely as possible to the form in which it was recorded and transcribed” (Bogdan and Biklen, 1982:28). But in this research are only used field notes, observation checklist and questionnaire. The class activities include the teacher and student’s activities during teaching learning process. The researcher described the teaching learning process, the use of STAD, and the students’ activities when they read narrative text, their responses to the material, etc. The subjects of the study was divided into two, namely the English teacher and the students in XI IPA3 of SMA Taruna Pembangunan Surabaya, related to the research questions. From the first research question which represent the interaction of teacher in applying STAD to teach a narrative text from its generic structure and language features, the subjects of study were the teacher andeleventh graders of SMA Intensif Taruna Pembangunan Surabaya. Based on the standard competency, narrative text was given in this grade The researcher chose SMA Intensif Taruna Pembangunan Surabaya with consideration of this school had ever applied STAD as one of teaching technique to be used to help students’ ability in reading activity of narrative text. The teacher also suggested XI IPA3to be the class that was going to be observed because this class has the most students who were interested in reading english texts. The students consist of 30 students, 9 boys and 21 girls. Research instrument is a means to collect the data. In this study, the instruments were observation checklist to describe the first research question and students speaking assessment task to describe the second research question. In this study, the researcher used non participant observation. The observation was done three times. The researcher presented in the classroom but did not interact or participate. He just observes and follows the teaching and learning process to see the teacher in applying folktale movie in teaching speaking in the class. There were three steps in analyzing the data in this research: In this research, the data of the study dealt with the students’ and teacher’s activity with STAD and students’ responses when they are taught with STAD in the classroom. In a research, data is the most important thing because data is the variable which is researched and has function as the verification of the hypothesis (Ismawati 2012:82). Therefore, good or bad of a data is to determine the quality of the result, while the truth of the data depends on the accuracy of the data collection instrument. Good instrument must have at least two important requirements, namely valid and reliable. According to Moleong (1990:19), to collect the data, scientific paradigms utilize a written test or questionnaire or using physical means such as polygraph and so on. The research instruments are used to collect the data. To get the information needed, some instruments have to be used. They are observation checklist, questionnaire and field notes. Observation checklist is used to describe the phenomena dealing with the implementation of STAD as a technique in teaching reading narrative text. The phenomena observed were including the points about material, the technique and the teaching and learning process. There were 3 major parts of observation checklist including teacher’s activities, the students’ activities, and the technique itself (STAD). The observation checklist for the teacher’s activities contained several points to be observed such as pre-activities, main activities, and evaluation. For further details, the researcher tried to present the table of the observation checklist in details (see appendix). There were fifteen questions for the teacher’s observation checklist. The first five questions were used to find out what the teacher did in the beginning of the lesson such as greeted the students, asked their condition, describing tasks, and the purpose of the study that day and included how the teacher encouraged their motivation to learn. While the second five questions, are made in order to gather information about what teacher do during main activities, during the teaching using STAD. The questions were about how teacher organized the class into groups and what she did when the students worked cooperatively during the implementation of STAD. And the last five questions were made to find out how the teacher evaluated the students. While for students, the researcher paid attention on what the students’ did during the teaching of STAD technique in teaching reading narrative. The observation for the students’ activities consists of several parts question written down in the observation checklist (see appendix). The questions were about students’ activities in each section such as pre-activities, main activities, and evaluation. There were also questions about how the students worked and discussed the material with other students during the STAD technique. For the STAD technique, the researcher also made an observation checklist to find out whether the technique used was appropriate to both students and the material. In this case, the researcher tried to look further how each group discussed, and what steps were involved in STAD process like reading, discussions, evaluation and teamwork (see appendix). There were two columns in observation checklist. The first column was the indicator and the second column was the place to give the sign check (Ö). The content of first column was indicators about the material, technique and the teaching learning process. The researcher put a check (Ö) when the activities in the first column was done. But if the activities were in the contrary, the researcher put dash (-). Questionnaire is a form which is made by researcher to get the information from the students. It is used to gather the information to find out what the students’ feel during the teaching STAD. The researcher gave the questionnaire sheet to the students at the end of the lesson. The questionnaire consists of fifteen questions. The detail question about questionnaire are presented below Table 1. Detail question in questionnaire No Indicator Number 1. Students’ preferences on English, reading, enthusiasm. 1, 2, 8 2. Students’ response on the implementation of STAD in teaching reading narrative. 3, 4, 5, 6, 7, 12, 13, 14, 15 3. Teacher’s role as motivator. 9, 10, 11 The data was collected through non-participant observation. It was an observation in which the researcher only observed the process of teaching and learning. The researcher had to keep his existence and not influenced the natural attitude or behavior of the subject of the study. It was done by using observation checklist and field notes. All the data (observation checklist, questionnaire and field notes) was presented or described into a description. The data was taken in each meeting. In order to gain information about the students’ feeling of STAD in reading narrative class, the researcher used questionnaire to the student. The data collected from the observation, questionnaire and field notes was evaluated through evaluated analysis and reported descriptively. The data from the observation, interview and field notes was analyzed. Afterwards, these data was arranged and classified into two broad categories. First was the data about how the teacher teaches using STAD teaching reading narrative text. Second was student’s response while learning with STAD in reading narrative class. The data was presented descriptively. At last, the researcher gave the conclusion about the research. RESULT AND DISCUSSION The Results of the Study Based on the observation checklist, field notes and questionnaire to the process of the application of STAD and the response of the eleventh Graders of SMA ITP Surabaya after being taught by STAD, the result is described as follows: The Application of STAD in Teaching Reading Narrative Text The first meeting was conducted on Monday, March 18th, 2013. It was conducted in XI IPA3. The researcher helped the teacher to design lesson plan to be implemented in the class. The material that was used in this meeting was “Why do Hawks Hunt Chicks?” In the first meeting, before the lesson started, the teacher greeted the students. After that, the teacher checked the students’ attendance by calling one by one and nobody was absent. There were 30 students in this class. Then, the teacher introduced the researcher and also explained the purpose of this research to the students. The researcher joined into the class for three meetings. Then the researcher sat in the back seat of the class The teacher started to explain about what the students would be learned in this meeting, namely reading narrative text and understanding it by using STAD technique. The students listen carefully to the teacher. After that, the teacher wrote the material on the whiteboard. The students copied it on their notebook. After it was finished, the teacher told the student that they would learn in easy way. Then the teacher repeated his question about the definition of narrative text. The students seemed busy to read aloud the definition that had been written ion their paper. The teacher tried to explain it clear by giving simple explanation to make students easier to understand. The next was generic structure. The teacher asked the students about generic structure of narrative text. One of the students answered it. Then the teacher wrote the generic structure on the white board. The teacher explained it by using simple word and used comparable words to narrative texts in Bahasa Indonesia. The students could now understand it better. Then the teacher started explaining STAD. The rule, the purpose and how the STAD would be applied in the class. After all students understood about narrative and STAD, the teacher divided the students into 6 groups. The students gathered with their group in no time. After that, the teacher asked the students to read individually the text that had been copied to their book for 5 minutes. In that 5 minutes, the teacher walked around the class into each group and found some students got some difficulties. After 5 minutes gone, the teacher asked the students to discuss with their own group. Each student must have different ability in English. The discussion has purpose to make sure that all students in that group understand the content of the text. In discussion session, all students share their knowledge about the text. So, it can be peer teaching session. The teacher reminded to the students to use English while discussing the text. The students started to discuss with their own group. Students shared their knowledge about the text. The students had to make sure that all students in their own group understood the material. The teacher moved around the class to check there was any students needed help or not. But most of the students still used Indonesian when they discussed the text. When the students were discussing the text, the problem was emerged. There was domination of certain student in a group. Clever student in the group dominated the discussion, while the other were only keep their silence and listened to the clever student. Then the teacher came to each group and explained to them that it was a teamwork not individual work. If they want to get better understanding, they had to learn and discuss together. After all students discussed the text for 20 minutes, the teacher started to finish their discussion. Then the teacher discussed the text with the students. The explanation session and classroom discussion was started. The teacher explained and discussed about the content of the text until the generic structure of the text with all students. The discussion lasted until the teacher discussed about the resolution. After that the teacher gave them quizzes and asked them to do it individually. STAD is basically done in team, but the real purpose is the student’s individually improvement. The teacher wrote the quizzes on the whiteboard and all students copied it on their notebook. The students had 30 minutes to do the quizzes and there were 10 questions in it. However, there were some students still discuss it with other students while doing the test. The teacher warned the students not to discuss with their friend, if so; the teacher would take their work immediately. It means that they would not get score. The students felt regret and the teacher forgave them and asked them to continue their work. After 30 minutes gone, the teacher asked the students to submit their works. Then the teacher ended the class for that day. The first meeting was conducted on Thursday, March 21th, 2013. It was conducted in XI IPA3. The material that was used in this meeting was “King of Mice and the Poor man.” But the title was not stated in the text. In the second meeting, before the lesson started, the teacher greeted the students. After that, the teacher checked the students’ attendance by calling one by one and nobody was absent. There were still 30 students in this class. The researcher still joined into the class in the second meeting. Then the researcher sat in the back seat of the class. The teacher asks the students about STAD and Narrative text. It has purpose to review the students’ memory from the meeting before. Then the teacher asked the students to gather with their group which had been made in the meeting before. The classroom condition is was crowded as the meeting before. It took longer time to get students to their group because they needed to remember their own group. After they sat with their own group, the teacher started to write the material on the whiteboard and asked the student to copy it on their notebook. Then after they finished writing it, the teacher asked the student to read the material for 5 minutes. The students seemed busy reading the material. After that, the teacher asked to discuss it like the meeting before. The students discussed the material. They started to share their idea about the text. Most of the students share about the difficult words in the text. They were busy to look for the meaning in the dictionary. There were some groups that brought no dictionary. They tried to borrow from other group. The teacher walked around the class to check if students had some difficulties. After all students discussed the text for 20 minutes, the teacher started to finish their discussion. Then the teacher discussed the text with the students. The explanation session and classroom discussion then started. The teacher explained and discussed about the content of the text until the generic structure of the text with all students. The students had their seat back. The teacher wrote the quiz on the white board and the students copied the material on their notebook. The students had 30 minutes to do the quizzes and there were 10 questions in it. After 30 minutes gone, the teacher asked the students to submit their works. There is still enough time to review the lesson. Then the teacher asked what the students had learned that day. The students answered all the questions given by the teacher. Then the teacher ended the class for that day. The third meeting was conducted on Monday March 25th 2013. It was conducted in XI IPA3. The material that was used in this meeting was “The Legend of Sura and Baya.” But the title was not stated in the text. In the third meeting, the last day of this research, before the lesson started, the teacher greeted the students. After that, the teacher checked the students’ attendance by calling one by one and nobody was absent. There were still 30 students in this class. The researcher still joined into the class in the third meeting. Then the researcher sat in the back seat of the class. The teacher asked the students whether they still remind narrative text and STAD technique. Most of students still remembered the narrative text and STAD technique. Then the teacher asked students to gather with their group. The students started to gather with their group in no time. Then the teacher gave the material to the students and started the lesson. The teacher asked the students to read the text. All students seemed busy reading the text. But there were some students who still talked with their friend. The teacher came to them to warn them. Then they continue reading. After reading session, the teacher asked the students to discuss with their friend. The students had to make sure that all members in each group had understood the material. The teacher moved around to see if there were students who needed help. After all students in every group understood The Legend of Sura and Baya, the teacher started to discuss together with all students in the class. Then the teacher gave the quizzes to the students. This last meeting, there is no one who cheated. The students were given 30 minutes to do the quizzes. After 30 minutes, the students had to submit their work. In this last meeting, the researcher gave questionnaire to the students. It has purpose to know students’ response about the teaching reading narrative text by using STAD. The students were noisy when they answered the questionnaire. The teacher then asked the students to keep silent while answering the questionnaire. The researcher also asked the students to do it by themselves. The teacher asked to submit the questionnaire to the researcher. After that, teacher ended the class. Students’ response after being taught by STAD Besides observing the application of STAD technique in the class, the researcher analyzes the students’ response after being taught by STAD in teaching reading narrative text. It was used to investigate how far students’ interest to participate the class during STAD technique was being implemented. The observation checklists were used to investigate the teacher’s activities, students’ activities and the STAD itself that was implemented in the class. The result of the teacher’s activity There were 3 major points used to measure the teacher’s activities when applying STAD technique. Based on the table of observation technique above, it showed that the activities done by teacher during the application of STAD technique was appropriate and suitable for the students. The best indicator that made STAD technique was appropriate was the teacher the teacher asked students to discuss with their friends. This activity made the students active because in the usual meeting (without STAD), the students always listened to the teacher and not being given chance to discuss anything with their friends. It made students more active since they were not shy when they are discussing with their own friend. Although some indicators were not done in the first and second meeting, all indicators were done in the third meeting. The result of the students’ activity Based on the table above, it showed that most students understood what the teacher asked them. They knew what they had to do in each activity. They completed the tasks even they still talked with their friends while doing the assignment in the first meeting. But in the second and the third meeting were good since they did the assignment individually. Basically, the students did all the indicators in the third meeting. The best indicators that made students get better knowledge in their class is the students helped each other in their group. The students felt that they studied together and they had the same difficulties. So the better abilities students helped the ordinary abilities students. The result of the application of STAD Based on the table above, it showed that the application of STAD was done completely. There are only two parts of the indicators that were not done, they are “the group has heterogeneous member based on students’ score” and “keep the silence while doing the assignment”. The failure of first indicator happened because the teacher forgot it and had divided the students into team based on their gender only. While the failure of second indicator happened because while the teacher gave the assignment, the teacher always left the class and let the students free to be out of control. The best indicator that made this technique appropriate was each member participated actively in the discussion. It made the students who were passive to be active. This were good since the students were not an object who always listen but they were a subject that need to be active The questionnaire was given to the students in the last meeting of the observation. There were 15 multiple choice questions which are included to several indicators, they are: THE RESULT OF QUESTIONNAIRE No Indicator Number Answers Percentage (%) Yes No Yes No 1. Students’ preferences on English, reading, enthusiasm. 1, 2, 8 69 21 76,7 23,3 2. Students’ response on the implementation of STAD in teaching reading narrative. 3, 4, 5, 6, 7, 12, 13, 14, 15 173 97 64,1 35,9 3. Teacher’s role as motivator. 9, 10, 11 61 29 67,8 32,2 Discussion of the Results The Application of STAD In teaching and learning process, when Students Team Achievements Division (STAD) was applied in teaching reading narrative text, the students in the first, second and third meeting were good. But there were several things that need to be noted down. In the first meeting, the students were still shy to discuss with their friends. It was caused by they wanted to be in the same group as gender. There were some students that were still discussing when they had their assignment. But the teacher was still able to control them. Compared to the result of first meeting, second meeting got a progress. Although students’ limited vocabulary was the problem in this meeting, the second meeting gave some improvement to the students reading. They could understand the text more easily than the first meeting. Some students did a protest to change their member of groups to member that they wanted, namely the same gender. But the teacher can handle it and kept the group to be the same as before. Beside that the teacher could manage time and applied the STAD technique better. He did almost all steps in implementing STAD technique. On the third meeting, the progress was remarkable. All students participated actively when they were discussing the text. They discussed and shared their idea with their own group. Although there were some students still dominated the discussion, each student still gave his/her opinion. Beside that, the students vocabulary became broad, even most of them did not open the dictionary while reading the text. It meant that they understood the meaning of vocabularies that vocabularies that were used in the text. Most of students could find the vocabulary of each paragraph correctly. In this observation, the researcher concluded that STAD technique can improve students’ reading ability to understand narrative text. Beside, students’ activeness improved significantly. Before using STAD, students only listened to the teacher and seem bored when they were in the class. When STAD was applied, the students can actively participate in the class. By being active, students got more knowledge in the class. Based on the observation during the research, it was clear that the use of STAD technique was effective to be used as teaching aids in reading narrative text. It was because of several considerations. First, the class atmosphere showed that the students were enthusiastic when they were discussing with their groups. Each group member were active to help other group member to understand the text. It meant that STAD not only provided an opportunity for students to understand the material, but also socialize with their peers. Second students said that STAD technique gave them inspiration to read narrative text. The groups would do their best to be the best group. It motivated them to read the text so that they could do the test. It meant that STAD could motivated students to learn. Students’ Response Based on analysis of the result of the questionnaire, it showed that the application of STAD technique was much appropriate to overcome students’ problem in reading narrative text. For example, after discussing with their group, students can identify generic structure, can share their vocabulary, find the main idea of each paragraph, and find specific information. The application of STAD helped the students to practice reading narrative text optimally. Furthermore STAD is an alternative method in teaching reading. The students were motivated in reading and they comprehend the text easily because they can ask their friend in their group. It is the idea of STAD that students in each group would help each other explained until all of member had understood the selected text completely. Moreover, it also can be a good method to engage the students’ participation in the class because allowed students to be active in the class. Students had chance to share their ideas with their friends in their group. This also a great help for students who are not good in English. Clever students could help them. The students should share what they knew about the text. When a student got information in the text, they had to tell other students in their group and helped to make all member of their group understand. Students were enthusiastic in cooperative working. Although for the first meeting they were passive, in the third meeting they were active. They took part in classroom discussion by sharing, responding, and answering their friend’s idea. Students were interested in reading narrative text through STAD technique because they had various activities in teaching and learning process. The application of STAD helped the students to overcome their difficulties in reading narrative text. They could learn how to motivate their friends, how to response their friends’ idea, and how to held peer teaching. Finally, the students stated hat the application of STAD technique in teaching reading of narrative text was very useful and helpful to overcome the students’ difficulty in reading narrative text. It gave positive effects on the students’ ability and achievement in reading narrative text. It was shown from the result of students’ response toward the application of STAD in their class. It could be concluded that the application of STAD technique in teaching reading of narrative text could gain the students’ interest to join the reading class so that they could comprehend the material. CONCLUSION AND SUGGESTION Conclusion Based on the result and discussion, it could be concluded from the result of observation checklist, field notes and questionnaire. Overall, the STAD technique applied by the teacher during the three times observation were very suitable and appropriate in teaching reading. The STAD technique gave the students lots of opportunities to discuss with their friend about the text and it makes them feel brave to ask about the text to their friend in their group. It also can create conducive atmosphere for the students to comprehend the text. Beside that, students can also develop their social skills when they interact with others. The important point is STAD is suitable to teach reading of narrative text in SMA. When they were discussing the text, every student helped each other. The students, who were able to understand the text fast, helped the students who were not able to understand the text fast. Each information they shared could be meaningful for others in order to do the quizzes. This situation could motivate the students to be more active in the discussion. The researcher found out that there were several factors which caused students were reluctant to share their idea when discussion session in the first meeting. Some students claimed that they keep their silence because they were lack of self-confidence. Some of them said that they were unable to speak by using English. Some of them just listen to the clever students in their group. But in the second and third meeting, the students started to feel confident to share their thought in the discussion session. The teacher’s role was to motivate them to speak and encourage them to discuss the text with their friend. When the students made a mistake, the teacher should correct them and not blaming them. So that, the problem faced by students can be solved. Overall, most of students liked learning by using STAD technique. It can be stated from the questionnaire that most of students gave their positive answer about STAD technique. Suggestion According to the result of the research, the researcher will give several suggestions which are should be considered by English teacher. Those suggestions are: Creating a conducive atmosphere on the class can raise the motivation of the students to learn. The students can easily understand and remember the lesson when they are learning in an interesting atmosphere. Providing new techniques for the students not only reduce the students’ boredom but also can give them to feel anxious to do the new technique of teaching and learning (in this case is STAD). Giving opportunities for students to discuss with their friend about the text is more effective since students will not be shy since they speak with their friend, not with their teacher. At last, the researcher hopes that this study will give its benefit to the reader and then the study would be developed by conducting the other research at the same field which can give contribution to the educational research REFERENCES Arends, Richard I. 1997. Classroom Instruction and Management. USA: McGraw-Hill Companies. Bogdan, Robert C. and Sari Knopp Biklen. 1982. Qualitative Research for Education: An Introduction to Theory and Methods. Sydney: Allyn and Bacon, Inc. Brown, Douglas. 2001. Teaching by Principles An Interactive Approach to Language Pedagogy. New York: Pearson Education Inc. Brown, Douglas. 2007. Prinsip Pembelajaran dan Pengajaran Bahasa. Jakarta: Kedubes AS. Brown, Douglas. 2004. Language Assessment: Principles and Classroom Practices. New York: Pearson Education Inc. Moleong, Lexy. 1990. Metodologi Penelitian Kualitatif. Bandung: PT Remaja Rosdakarya. Harmer, Jeremy. 2001. The Practice of English Language Teaching. England: Pearson Education Limited. Huda, Miftahul. 2012. Cooperative Learning: Metode, Teknik, Struktur, dan Model Penerapan. Yogyakarta: Pustaka Pelajar. Nasution, S. dan Thomas M. 2008. Buku Penuntun Membuat Tesis, Skripsi, Disertasi, dan Makalah. Jakarta: PT. Bumi Aksara. Nunan, David. 1991. Language Teaching Methodology: a Textbook for Teacher. Great Brittain: Prentice Hall International (UK) Ltd. Richards, Jack C. and Thodore S. Rodgers. 2001. Approaches and Methods in Language Teaching. USA: Cambridge University Press. Simanjuntak, Edithia Gloria. 1988. Developing Reading Skills for EFL Students. Jakarta: Depdikbud Dikti. Tarigan, Henry Guntur. TT. Membaca Sebagai Suatu Keterampilan Berbahasa. Bandung: Angkasa. Yusron, Narulita. 2005. Cooperative Learning: Teori, Riset dan Praktik. Ban